Computational Fluid Dynamics (CFD) Modeling Study of Thermal Performance for Multipurpose Solar Heating System - Al-Abbas, Audai Hussein (Al-Nahrain Journal for Engineering Sciences, 2017)
The 3-D numerical simulations of the thermal collectors in solar heating systems were conducted to simulate the conventional solar heating system, multipurpose solar water heater (MPSWH), and multipurpose solar air heater (MPSAH). The commercial computational fluid dynamics (CFD), AVL Fire ver. 2009.2 was used to solve and investigate the temperature distributions in the absorber plate and riser tube of both solar water and air heater during summer and winter seasons. The RNG k -turbulence model was employed for this CFD study. The present paper was to provide a good understanding of thermal performance for the solar collector at different operating conditions. The experimental setup and physical data of Venkatesh, R. and Christraj, W. [15] were employed as geometric parameters and initial boundary conditions to model and to validate the predicted numerical values. Comparing to the values of temperatures for the conventional SWH and SAH, the predicted results of the MPSWH and the MPSAH showed a good improvement on the thermal performance. These enhancements on the temperature may have been due to the new design adopted in the multipurpose solar heating systems by using riser tubes and headers to the original design of the thermal systems. Additionally, the thermal performance of solar collectors increases with increasing the mass flow rates and thermal conductivity of absorber plate. For validation aspect, the predicted results of all cases examined showed a good agreement against the measured results in terms of temperature distribution levels and thermal efficiencies.